Employability Skills in the TVET Trainer Training Program: The perception Between Experienced Trainers and Novices Trainers - Wan Abdullah, Wan Fadzilah; Mohd Salleh, Kahirol; Sulaiman, Nor Lisa; Kamarrudin, Mahazrul (Journal of Technical Education and Training, 2022)
This paper is aimed to determine the importance of employability skills among experienced and novice trainers in the TVET trainer training program. This is due to, some employers reported TVET graduates’ lack of employability skills and facing difficulties to fulfil the current employment demands and professional expectations needed by industries (e.g., people management skills, communication skills, interpersonal skills, teamwork, professionalism, knowledge, and principles, problem-solving skills, and decision-making skills). A survey questionnaire was distributed during the TVET training program. A total of Experienced Trainers (n=34) and Novice trainers (n=137) were participating in this study. This study ranked the 25 abilities/items according to eight main constructs of employability skills based on a score ranging from (1) – to (5). The findings indicated that there is a different rank of employability skills between experienced and novice trainers. From these findings, it shows that communication skills, teamwork skills, self-discipline skills, and interpersonal skills are equally perceived to have a high importance level (top 4 highest) by both experienced trainers and novice trainers, while leadership skills, learning skills, and conceptual skills are equally perceived to have a lower importance level according to both experienced trainers and novice trainers. This calls for the planning of a specific curriculum that can be integrated into the TVET trainer training curriculum. It is necessary to transform the educational institutes into lifelong education centres to facilitate this employability skills formation among the graduates. In embedding the employability skills into the curriculum, teaching, learning, and assessment processes, steps must be taken to ensure that there is a constructive alignment between them. The desired employability skills should be made explicit through the learning outcomes of the modules that lead to high academic standards, leadership, industry-defined work readiness, and advanced and continuing education.